Racemic Salsolinol and its Enantiomers Act as Agonists of the μ-Opioid Receptor by Activating the Gi Protein-Adenylate Cyclase Pathway - Berríos-Cárcamo, Pablo; Quintanilla, María E.; Herrera-Marschitz, Mario; Vasiliou, Vasilis; Zapata-Torres, Gerald; Rivera-Meza, Mario (Frontiers in Behavioral Neuroscience, 2017)
Background: Several studies have shown that the ethanol-derived metabolite salsolinol (SAL) can activate the mesolimbic system, suggesting that SAL is the active molecule mediating the rewarding effects of ethanol. In vitro and in vivo studies suggest that SAL exerts its action on neuron excitability through a mechanism involving opioid neurotransmission. However, there is no direct pharmacologic evidence showing that SAL activates opioid receptors. Methods: The ability of racemic (R/S)-SAL, and its stereoisomers (R)-SAL and (S)-SAL, to activate the μ-opioid receptor was tested in cell-based (light-emitting) receptor assays. To further characterizing the interaction of SAL stereoisomers with the μ-opioid receptor, a molecular docking study was performed using the crystal structure of the μ-opioid receptor. Results: This study shows that SAL activates the μ-opioid receptor by the classical G protein-adenylate cyclase pathway with an half-maximal effective concentration (EC50) of 2 × 10−5 M. The agonist action of SAL was fully blocked by the μ-opioid antagonist naltrexone. The EC50 for the purified stereoisomers (R)-SAL and (S)-SAL were 6 × 10−4 M and 9 × 10−6 M respectively. It was found that the action of racemic SAL on the μ-opioid receptor did not promote the recruitment of β-arrestin. Molecular docking studies showed that the interaction of (R)- and (S)-SAL with the μ-opioid receptor is similar to that predicted for the agonist morphine. Conclusions: It is shown that (R)-SAL and (S)-SAL are agonists of the μ-opioid receptor. (S)-SAL is a more potent agonist than the (R)-SAL stereoisomer. In silico analysis predicts a morphine-like interaction between (R)- and (S)-SAL with the μ-opioid receptor. These results suggest that an opioid action of SAL or its enantiomers is involved in the rewarding effects of ethanol.